(3JNdjU GdEfSGf ef XdeGJ GdONGfs - (3YHO GdfGaYs ((3eMeO GdeaJjs)
(3ChdgG (B:s
(3GdMeO ddg GdPj MQe Ydi YHGOg GdNHGFK CeG HYO deG TGYJ GdHOYI GdNHjKI CYfj GSJYeGd GdJfHGc hTQH ONGfg Hjf GdYHGO CQOJ Cf CcJH QSGdI aj HjGf MQeI gPg GdHOYI hSejJgGs
(3BNQgG (B:s
(3hdG Tc Cfg NHjK Hd gh CNHK hWHYj eSJbPQ heSJNHK hdG jfcQ NHKg EdG GdZhjs
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
(3MGdI GdfSNI (B:s
Keywords: (3GdeYGQa GdYGeIs